Caregivers’ Satisfaction toward Under-Five Health Care Services Provided at Primary Health Care Centers in Al Karkh, Baghdad, 2020 - Bahaa Al Deen, Lamia D.; Fadhel, Abeer Abdulkareem (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Satisfied caregivers are more likely to return for further care and to recommend the primary health care center services to others. Satisfied caregivers usually are compliant with the medical provider advice and the recommended treatment plan. Compliance will eventually lead to better health outcomes.Method: A cross-sectional study with an analytic element was conducted during the period from the beginning of July to the end of September 2020. A convenient sample was collected from six primary health care centers in Al-Karkh side of Baghdad city where caregivers who attend those centers with their children for under-five health care services were interviewed using a structured questionnaire.Objective: To measure the caregivers’ satisfaction toward under-five health care services at primary health care centers in Baghdad Al-Karkh and their association with certain socio-demographic characteristics.Results: A total of 500 caregivers were interviewed during the study period, the overall satisfaction was (64%). Caregivers were satisfied with primary health care centers cleanliness (77.8%), while they were highly dissatisfied with the communication with the nurses (78.8%), with the waiting time for a routine visit (74.6%), with nurses’ antiseptic methods (59.2%), and with the availability and adequacy of their children’s vaccines (65.4%).Conclusions: The level of satisfaction of caregivers with under-five health care services provided at primary health care centers was relatively low. The study revealed that the less educated and older caregivers showed a significant higher level of satisfaction.